Sustainable Entrepreneurship: The Potential of Campus Waste in Making Entrepreneurial Products with High Selling Value - Novembrianto , Rizka; Mirwan, Mohamad; Ervina, Dea Febrica; Sholikhah, Mar'atus; Wicaksono, Pandu (Nusantara Science and Technology Proceedings, 2023)
UPN "Veteran" Jawa Timur is one of the campuses in East Java. Various types of waste are produced on campus, including organic waste (used rice, used vegetables, tree branches, leaves, etc.) as well as inorganic waste, one of which is medical mask waste. The existence of these wastes will increase along with increasing human growth, in this case, student enrollment on campus. Therefore, waste processing must be carried out to reduce the generation and impacts that will result. One alternative for processing waste is recycling it into products with high selling value. This community service aims to show that the waste produced can be made into products that have high selling value such as soap from used cooking oil, maggots for fish food, local microorganisms, trash cans from used masks, pots from used masks, candles aromatherapy from used cooking oil and tumbler bottles to reduce use plastic bottles and compost. The method used in community service activities carried out at the UPN "Veteran" Jawa Timur campus is to create solutions for managing the waste produced to solve existing problems. The solution is in the form of creating entrepreneurial products as mentioned previously. The result of this community service has been running smoothly and well. The products made have high selling value. This is proven by the entrepreneurial activities that have been carried out showing that these products are in demand by the public.